Before porn was legal : the erotica empire of Beate Uhse - Heineman, Elizabeth D. 1962- (Univ. of Chicago Press, 2011)
Prelude: The Beate Uhse myth -- Introduction: Sex, consumption, and German history -- The permissive prudish state -- The economic miracle in the bedroom -- Interlude: The Beate Uhse myth -- The sex wave -- The porn wave -- Postlude: The Beate Uhse myth -- Interviews